The Relationship Of The Completeness Of Filling In Medical Records With The Quality Of Medical Record Documents In Inpamentation Patients At Grandmed Lubuk Pakam Hospital In 2023 - Okta Vealina Siahaan (Medistra Medical Journal (MMJ), 2023)
Medical records are one of the important parts in shaping the implementation of service delivery to patients in hospitals. Completeness of filling out medical records that are accurate, complete, and timely is needed in health services to fulfill the requirements in medical record management. Completeness of filling out medical records with the quality of medical record documents has a very significant role where the higher the completeness of filling out medical records, he higher the quality of medical record documents. This study aims to determine the relationship between the completeness of filling out medical records and the quality of medical records document for inpatients at Grandmed Lubuk Pakam in 2023. The method used in this research is analytic observational with cross sectional research design. The population of thes study were all medical record files of inpatients and sampling using simple random sampling technique as many as 77 files. The study was conducted by checking the observation sheet on the medical record files of hospitalized patients. Data analysis of this study used chi square test with 95% confidence level, (? = 0,05). The results showed that there was a retionship between the completenees of medical record filling and the quality of medical record documents for inpatiens ( p = 0,001 > 0,05 ). It is hoped that hospital will pay more attention to the completeness of filling out medical records on each sheet (form) in order to improve and maintain the quality of hospital services.